New Insights into the Role of Peroxisome Proliferator-Activated Receptors in Regulating the Inflammatory Response after Tissue Injury - Miriam D. Neher; Sebastian Weckbach; Markus S. Huber-Lang; Philip F. Stahel (PPAR Research)
Major trauma results in a strong inflammatory response in injured tissue. This posttraumatic hyperinflammation has been implied in the adverse events leading to a breakdown of host defense mechanisms and ultimately to delayed organ failure. Ligands to peroxisome proliferator-activated receptors (PPARs) have recently been identified as potent modulators of inflammation in various acute and chronic inflammatory conditions. The main mechanism of action mediated by ligand binding to PPARs is the inhibition of the nuclear transcription factor NF-κB, leading to downregulation of downstream gene transcription, such as for genes encoding proinflammatory cytokines. Pharmacological PPAR agonists exert strong anti-inflammatory properties in various animal models of tissue injury, including central nervous system trauma, ischemia/reperfusion injury, sepsis, and shock. In addition, PPAR agonists have been shown to induce wound healing process after tissue trauma. The present review was designed to provide an up-to-date overview on the current understanding of the role of PPARs in the pathophysiology of the inflammatory response after major trauma. Therapeutic options for using recombinant PPAR agonists as pharmacological agents in the management of posttraumatic inflammation will be discussed.